Secondary Metabolites of Plant Origin Containing Carbazole as Lead Molecule: A Review - Sharma, Atul; Pathak, Devender (Current Traditional Medicine, 2021)
The continuous attempt of drug discovery and search for a potential drug molecules with promising pharmacological activities is always of immense interest. Most of those chemical compounds having active pharmacological effects contain heterocyclic nucleus or compounds. Heterocyclic compounds clutch a particular place among pharmaceutically active natural and synthetic compounds. The ability to serve both as biomimetics and reactive pharmacophores of the heterocyclic nucleus is incredible and principally contributed to their unique value as traditional key elements of many drugs. These heterocyclic nuclei offer a huge area for new lead molecules in drug discovery and for the generation of activity relationships with biological targets to enhance their pharmacological effects. In the heterocyclic nucleus, the hydrogen bond acceptors and donors arranged in a manner of a semi-rigid skeleton in heterocyclic rings and therefore can present a varied display of significant pharmacophores. Lead identification and optimization of a probable drug target can be achieved by the generation of chemically diverse heterocyclic pharmacophores with different groups or substituents. Herein, an attempt is made to review and summarize the naturally occurring carbazole containing alkaloids obtained from Murraya, Causena and Glycosmis species and their potential towards anticancer activity. Carbazole is a tricyclic heterocyclic molecule and an integral part of naturally occurring alkaloids possessing various potential biological activities such as anticancer, antimicrobial and antiviral. Due to the high binding affinity of carbazole towards nucleic acid/ receptor and mimicking their biological activity, carbazole derived alkaloids exhibit the potential cytotoxic effect.
Keywords: glycosmis